Respuesta :
We know what y is given the second equation, so let’s plug it in
5x - (2x - 4) = 40
Solve for x
5x - 2x + 4 = 40
3x = 36
x = 12
Plug in x for either equation
y = 2(12) - 4
y = 24 - 4
y = 20
X = 12 and Y = 20, so D
5x - (2x - 4) = 40
Solve for x
5x - 2x + 4 = 40
3x = 36
x = 12
Plug in x for either equation
y = 2(12) - 4
y = 24 - 4
y = 20
X = 12 and Y = 20, so D
Answer is D
{ solve simultaneously }
rearrange equation to make y the subject
5x-y=40
y=5x-40
Sub y=5x-40 into the second equation given ( y=2x-4 )
5x-40 = 2x-4
Solve normally to find x
x = 12
Sub x=12 into y=5x-40
Solve normally to find y
y = 20
Therefore, answer is D) 12, 20
{ solve simultaneously }
rearrange equation to make y the subject
5x-y=40
y=5x-40
Sub y=5x-40 into the second equation given ( y=2x-4 )
5x-40 = 2x-4
Solve normally to find x
x = 12
Sub x=12 into y=5x-40
Solve normally to find y
y = 20
Therefore, answer is D) 12, 20